Infinitely many solutions for a gauged nonlinear Schrödinger equation with a perturbation - Xu, Jiafa; Liu, Jie; O'Regan, Donal (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, we use the Fountain theorem under the Cerami condition to study the gauged nonlinear Schrödinger equation with a perturbation in R2. Under some appropriate conditions, we obtain the existence of infinitely many high energy solutions for the equation.